2012
DOI: 10.1016/j.jpeds.2011.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept and Sodium Thiosulfate for Treatment of Recalcitrant Juvenile Dermatomyositis Complicated by Ulceration and Calcinosis

Abstract: We report the successful use of abatacept and sodium thiosulfate in a patient with severe recalcitrant juvenile dermatomyositis complicated by ulcerative skin disease and progressive calcinosis. This combination therapy resulted in significant reduction in muscle and skin inflammation, decreased corticosteroid dependence, and halted the progression of calcinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 11 publications
0
61
0
1
Order By: Relevance
“…This highlights a limitation of our study because patients received etanercept therapy for only 12 weeks, which may have been insufficient to detect either improvement or worsening of disease activity. A recent report of abatacept and sodium thiosulfate administered to a 14-year-old female with resistant juvenile DM involving calcinosis and ulceration resulted in marked disease improvement (18). Future clinical trials of abatacept, rituximab, and other therapies with a biologic agent in children with juvenile DM are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights a limitation of our study because patients received etanercept therapy for only 12 weeks, which may have been insufficient to detect either improvement or worsening of disease activity. A recent report of abatacept and sodium thiosulfate administered to a 14-year-old female with resistant juvenile DM involving calcinosis and ulceration resulted in marked disease improvement (18). Future clinical trials of abatacept, rituximab, and other therapies with a biologic agent in children with juvenile DM are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Later, an improvement in muscle and skin disease was reported in a patient with juvenile DM complicated by ulceration and calcinosis [69]. Recently, Kerola et al [70] reported a case of a 46-year-old female patient who developed a severe myositis overlap syndrome, including features of RA, peripheral vasculitis and ILD, refractory to different immunosuppressive and biologic drugs.…”
Section: Biologic Therapymentioning
confidence: 98%
“…A recently published review of current pharmacological treatment of idiopathic inflammatory myopathies [69] described three cases of refractory myositis treated with tocilizumab with promising results [118][119][120] and three case reports showing beneficial effects of co-stimulation blockade using Abatacept in myositis [121][122][123]. A randomized clinical trial is underway to test this hypothesis (ClinicalTrials.gov Identifier: NCT02594735).…”
Section: Other Biologic Agentsmentioning
confidence: 99%